Perancangan Sistem Informasi Pengendalian Kualitas pada Laboratorium Proses IV PT X - Yuliandra, Berry; Wulan, Ratri Fradinda (Jurnal Optimasi Sistem Industri, 2018)
Effectiveness and efficiency can improve the performance of manufacturing companies. Such improvements can be achieved through the application of web-based applications. PT X is one of cement producers in Indonesia and to maintain its competitive advantage, PT X establishes several Process Laboratory responsible for its product quality control activities. One of them is Process Laboratory IV. Process Laboratory IV is still using spreadsheet based information system so that most of the activities and evaluation are still run manually. Some weaknesses are still encountered such as slow information flow rates, minimum levels of information security, and the potential for various forms of fraud. This research was conducted to design more efficient quality control information system through implementation of web based application. The information systems design created by building: (a) Business process diagrams (b) Use case diagrams, (c) Class diagrams, (d) Entity relationship diagrams, and (e) Databases, followed by web-based application design based on the results of information system design. The system design involves four actors with different authority and access levels to minimize information security issues. Through these conditions various forms of fraud can also be minimized. In addition, the system design also improves the information flow efficiency by eliminating the activity of re-input set point data. It can be concluded that the design of information systems with web-based applications have been able to help improve efficiency and minimize the weaknesses of current existing information systems in the PT X Process Laboratory IV.